Reaksi Pasar Modal terhadap Faktor Ekonomi dan Faktor Non Ekonomi di Indonesia - Ninda Vani Lestari; Ris Yuwono Nugroho (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
The purpose of this study is (1) to examine how much influence economic and non-economic factors have on the movement of the Jakarta Composite Index (CSPI), (2) to examine the most dominant factor in the movement of the Composite Stock Price Index (CSPI). The method in this study uses monthly data and is processed using the Vector Auto Regression (VAR) analysis technique. the results of the variance decomposition test before social / political turmoil showed that the most dominant contribution was recorded at the CSPI itself 61 percent, with economic factors 21 percent and non-economic factors 18 percent. However, the results of the variance decomposition test after social / political turmoil showed that the most dominant contribution was recorded in non-economic factors, 52 percent, with economic factors 36 percent, and CSPI itself at 18 percent. Thus, there are differences before and after social / political turmoil